(2023)DISEÑO Y DESARROLLO DE UN CHOCOLATE FUNCIONAL CON INCORPORACIÓN DE CANNABIDIOL (CBD) CON FINES MEDICINALES.Quevedo.UTEQ.106p. - Mazacon Galeas , Jasury Fernanda (2023)
Functional chocolates are products that have been enriched with bioactive compounds or a higher content of cocoa solids in order to increase the amount of antioxidants present and achieve health benefits beyond pleasure and flavor. The purpose of this research is to design and develop a functional chocolate with the incorporation of Cannabidiol (CBD) for medicinal purposes using a Central Compound Design (DCC) or response surface with two study factors A and B, in which factor A: represents the concentration of cocoa, and factor B the concentration of CBD. For which analyzes were carried out to determine the content of flavonoids and total polyphenols; antioxidant activity by the FRAP and ABTS method; CBD and THC content; hedonic and descriptive sensory analysis. The statistical analysis for the bioactive components did not present a significant difference in the study factors, so the concentration of cannabidiol and cocoa solids contribute to increasing the functional properties of the chocolates. While the CBD content present in chocolates is only linked to the amount incorporated into the formulation. The best functional properties for all the analyzes of bioactive compounds (polyphenols, flavonoids, FRAP and ABTS) were obtained by the THSC treatment (77.07% cocoa solids, 300 mg kg-1 CBD), however in the sensory analysis, (flavor parameter) Statistically, the TBSA treatment (50% cocoa solids, 500 mg kg1 CBD) presented greater acceptance by tasters, so even though the developed chocolate presents good functional properties, it is of crucial importance that be pleasing to future consumers.